2016
DOI: 10.1007/s40520-016-0630-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tooth loss on walking speed decline over time in older adults: a population-based cohort study

Abstract: Background Tooth loss has been linked to poor health such as chronic diseases and mobility limitations. Prospective evidence on the association between tooth loss and walking speed decline is however lacking.AimsTo examine the impact of tooth loss on walking speed over time and explore whether inflammation may account for this association.MethodsThis study included 2695 persons aged 60 years and older, who were free from severe mobility limitation at baseline. Information on dental status was assessed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 35 publications
2
33
3
1
Order By: Relevance
“… 12 showed that OH problems predicted the development of depression. An evidence from Sweden suggested that losing teeth was associated with a decline in walking speed over time 13 . Vice versa, depression in younger ages is strongly associated with the chewing function at later ages 14 whereas declining function ability over time is a risk of having chewing difficulties 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 12 showed that OH problems predicted the development of depression. An evidence from Sweden suggested that losing teeth was associated with a decline in walking speed over time 13 . Vice versa, depression in younger ages is strongly associated with the chewing function at later ages 14 whereas declining function ability over time is a risk of having chewing difficulties 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Possible confounders were chosen for their potential associations with the outcomes of interest based the findings of previous studies. [6][7][8][9] The Table 1 shows the baseline characteristics of the groups with and without posterior occlusal support without matching. There were no significant differences between groups in terms of economic status, smoking habits, history of stroke, CRP level, MoCA-J score, or walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…PSM was used to address the large differences in sample size and baseline characteristics in the study population. Possible confounders were chosen for their potential associations with the outcomes of interest based the findings of previous studies . The predicted PS was calculated based on a logistic regression model, which estimated the probability of losing posterior occlusal support as a function of all relevant variables (sex, years of education, economic status, smoking habits, history of stroke, CRP level, height, weight, grip strength, MoCA‐J score and walking speed at baseline).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…tem uma relação significativa com o baixo peso, por exemplo, foi relatado que os participantes que estavam abaixo do peso mastigavam mais assimetricamente e mais lentamente do que os participantes com peso normal ou obesos(Song et al, 2017). A doença periodontal e a perda de dente têm sido associadas a deficiências de funções físicas, como fraca força muscular e limitações de mobilidade(Welmer et al, 2017) Okamoto et al, 2017)…”
unclassified